Mastoid Obliteration With Freeze-Dried Bone Allograft in Canal Wall Down Tympanoplasty: Description of a Novel Technique and Case Report - Antonio Faita; Giulia Montagner; Diletta Trojan; Valerio Maria Di Pasquale Fiasca (Case Reports in Surgery)
Mastoid obliteration can be performed after canal wall down (CWD) mastoidectomy with various materials. Homologous bone tissue harvested from cadaver donor represents a feasible option with advantages. The purpose of the study is to describe the case of a patient diagnosed with middle ear cholesteatoma treated with mastoidectomy of the CWD and mastoid obliteration with homologous freeze-dried corticocancellous bone particulate in the Cittadella Hospital Ear, Nose, Throat (ENT) unit. The preoperative characteristics of the patients, the procurement and processing of bone allografts, the surgical technique, and postsurgical outcomes are described. No perioperative and postoperative complications were observed, and no rejection or foreign body reactions occurred. The patient then underwent a seriated follow-up. Audiometric tests showed an improvement in hearing levels. The volume of the neoexternal ear canal was 2.01 cm3. The case demonstrated clinical stability, substantial hearing recovery, and no need for specialist cleaning of the reformed external ear canal (EEC). The freeze-dried bone tissue allograft, in the technical way we used, appears to be a viable option in mastoid obliteration because homologous bone is not affected by material shortage, has fast assimilation, and ensures a useful radiological examination scan, at a low cost.